MANAGEMENT OF SCHOOL COMMUNITY RELATIONSHIP PROGRAM IN INCREASING COMMUNITY PARTICIPATION AT SMAN 1 AMPANA KOTA, TOJO UNA-UNA REGENCY - Siti Rahma A. Lamadadju; Novianty Djafri; Besse Marhawati (Review of International Journal Education and School Leadership, 2025)
The Management of School–Community Relations Program to Enhance Community Participation (At SMAN 1 Ampana Kota). This research aims to describe: (1) the planning of the school–community relations program; (2) the implementation of the school– community relations program; (3) the impact of the school–community relations program; and (4) the supporting and inhibiting factors of the school–community relations program. This study uses a qualitative approach. Data collection techniques include interviews, documentation studies, and observations. The data analysis process involves data collection, data condensation, data presentation, and conclusion drawing. The results of the study show that: (1) The planning of the school–community relations program at SMAN 1 Ampana Kota is carried out through several stages, including planning, socialization, activity implementation, and evaluation. The school applies a collaborative approach with the community to achieve the program’s objectives; (2) The implementation of the school–community relations program involves the active roles of teachers and school staff in organizing activities and building effective communication with the community to foster active participation and support the sustainability of the program; (3) The impact of the school–community relations program on community participation includes increased community involvement in various school activities, such as parent meetings, social events, and school facility improvements. Moreover, this program has also shifted community perceptions about education. The community is increasingly aware of the importance of their contributions in supporting their children's education, which is reflected in their growing participation in school-organized activities; (4) The supporting and inhibiting factors of the school–community relations program include supporting factors such as awareness of the program's benefits, open communication between the school and the community, and the success of previous activities. Inhibiting factors include the community's limited time, lack of understanding of the program’s objectives, and geographical distance, which makes it difficult for some community members to attend school events. To overcome these obstacles, the school has taken measures to adjust activity schedules, improve socialization about the program's objectives, and provide better access for community members.